Wind loads on low-slope roofs of buildings with large plan dimensions. (15th December 2020) - Aldoum, Murad; Stathopoulos, Ted
Abstract: Wind load provisions in the North American codes and standards incorporate the results of wind tunnel studies and the full-scale measurements of wind loads. These studies examined wind effects on buildings with regular plan size, i.e. less than 60 m. This fact emphasizes the importance of testing large buildings in the wind tunnel and highlights the necessity of investigating the applicability of the North American code and standard provisions to large buildings. In the present study, three building models were constructed at a length scale of 1:400 with identical plan dimensions (equivalent to 118 m × 118 m) and different heights (equivalent to 5 m, 10 m and 20 m). The models were tested in simulated open country and suburban exposures. The experimental results were compared with full-scale data and the wind provisions of the North American codes and standards. It was found that the external peak pressure coefficients recommended by ASCE 7-16 (2017) are much higher than the experimental findings whereas those recommended by ASCE 7-10 (2010) are consistent with the experimental results. However, the experimental results indicate that the corner zone should be better defined as an L-shape for large buildings of 8 m height or more and the wind loads developed on the roof corner are approximately equal to those on the edge zone for large buildings of height less than 8 m.